A grammar of Fwe - Gunnink, Hilde (Language Science Press, 2022)
This book provides a first-ever comprehensive overview of the grammatical structure of Fwe. Fwe is a Bantu language spoken on the border between Zambia and Namibia, by some 20,000 people. Very little previous documentation exists on the language, and the current description of Fwe is based exclusively on newly collected field data. It includes an analysis of the grammatical structure of Fwe, followed by basic cultural information on greetings, a Fwe narrative with its English translation, and a lexicon comprising some 2200 Fwe lexemes with their English translation. This book is intended as a resource for linguists, whether interested in African languages, Bantu languages, language typology, or general linguistics.